(3EOGQI GdeDSSGJ GdCefjI habG deHGOF GdEOGQI GdMOjKI (B/s - (3YHO GdYdj, Ydj CHh GdThfs ((3YeGf, GdeecdI GdCQOfjI GdgGTejI (B:s (3OGQ OLdI fGTQhf hehRYhf,s, 2023)
(3jJfGhd GdcJGH ehVhY GdeHGOF GdEOGQjI GdMOjKI ddeDSSGJ GdCefjI MjJ jMcj Yf Cfg HMce GdeJWdY GdMGdj ddcKjQ ef GdJWhQGJ hGdJZjQGJ hGdJMOjGJ GdeJSGQYI, hJQJjHgG, hGdeYbOI aj JOGNdGJgG, hGdJj JhGLggG GdefXeGJ hGdeDSSGJ cGaI CfhGYgG hCTcGdgG aj GdhMOI GdKGfjI aj YGde GdCYeGd, aGdeDSSGJ GdeYGUQI, hgj cjGfGJ SQjYI heaGLFI aj HjFJgG GdOGNdjI hGdNGQLjI, hPdc dCSHGH eMdjI Ch GbJUGOjI Ch EbdjejI Ch YGdejI, eeG jLYdgG JJSe HSeGJ ZjQ eJhbYI ef GdJZjjQ, eeG jDOj Edi GgJeGe GdeeGQS HJZWjJgG, dcj JTed cGaI GdeDSSGJ HZV GdfXQ Yf MLegG Ch cdcgG GdEfJGLjI Ch WHjYI YedgG, hCjVG HehGcHI CNQi eJWhQI, JTYQ GJLGg CYeGdgG GdeYjfI hJYcS LhGfHgG cGaI, HGdEVGaI Edi hVY GSJQGJjLjGJ dJNWjWgG, dPdc, JYJHQ EOGQI GdeDSSGJ GdMOjKI gj ef CfhGY GdCYeGd GdegeI, JJWdH eJWdHGJ hGMJjGLGJ GdeDSSI(B.s
(3JUeje GdZdGa (B: (3NVjQ(B.s
(3ebQQGJ OQGSjI (B2025-2026.s
(3HHdjhLQGajI (B: (3UaMI (B227-300.s
Keywords: (3GdCef GdOGNdjs -- (3EOGQIs; (3GdeDSSGJ GdYGeIs -- (3EOGQIs